THE EFFECT OF SOCIAL ECONOMIC FACTORS ON FARMER BEHAVIOR IN RICE FARMING IN SUMBER KULON VILLAGE, JATITUJUH DISTRICT, MAJALENGKA REGENCY - Muhammad Nasirudin; Wulan Sumekar; Tutik Dalmiyatun (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
Farmers' behavior indicates someone already knows good knowledge, attitude and skills in rice farming activities. the purpose of this study is the influence of socio-economic factors on the behavior of farmers in rice farming. This research was conducted on 21 September - 10 November 2019 in Sumber Kulon Village, Jatitujuh District, Majalengka Regency, West Java. The method used in this study is a survey with 240 respondents. Data collection techniques using questionnaires and interviews, while data analysis techniques using descriptive analysis and multiple linear regression analysis. Patani activities in rice farming are started from land preparation, selection of rice seeds, rice seedbed, planting, maintenance, food and post-harvest. The results showed that the influence of socio-economic factors on farmer's behavior in the level of siginification was 0.05 with 0.006, Educational variable was 0.094, experience variable was 0.552, motivation variable was 0.034, acceptance variable was 0.096, media information variable was 0,000 and agricultural extension variables were of 0.010. This can be seen from the contribution of farmers in social factors by 27% of the behavior of farmers because farmers only depend on rice farming activities. The reasons for choosing to keep doing this activity are, among other things, a family business.